RalA-exocyst-dependent Recycling Endosome Trafficking Is Required for the Completion of Cytokinesis - Xiaowei Chen; Mayumi Inoue; Shu C. Hsu; Alan R. Saltiel (2006)
In eukaryotic cells, recycling endosome-mediated trafficking contributes to the completion of cytokinesis, in a manner under the control of the centrosome. We report that the exocyst complex and its interacting GTPase RalA play a critical role in this polarized trafficking process. RalA resides in the recycling endosome and relocates from the pericentrosomal region to key cytokinetic structures including the cleavage furrow, and later, the abscission site. This event is coupled to the dynamic redistribution of the exocyst proteins. These associate with the centrosome in interphase and concentrate on the central spindle/midbody during cytokinesis. Disruption of RalA-exocyst function leads to cytokinesis failure in late stages, particularly abscission, resembling the cytokinesis defects induced by loss of centrosome function. These data suggest that RalA and the exocyst may regulate vesicle delivery to the centrosome-related abscission site during the terminal stage of cytokinesis, implicating RalA as a critical regulator of cell cycle progression. In eukaryotic cells, recycling endosome-mediated trafficking contributes to the completion of cytokinesis, in a manner under the control of the centrosome. We report that the exocyst complex and its interacting GTPase RalA play a critical role in this polarized trafficking process. RalA resides in the recycling endosome and relocates from the pericentrosomal region to key cytokinetic structures including the cleavage furrow, and later, the abscission site. This event is coupled to the dynamic redistribution of the exocyst proteins. These associate with the centrosome in interphase and concentrate on the central spindle/midbody during cytokinesis. Disruption of RalA-exocyst function leads to cytokinesis failure in late stages, particularly abscission, resembling the cytokinesis defects induced by loss of centrosome function. These data suggest that RalA and the exocyst may regulate vesicle delivery to the centrosome-related abscission site during the terminal stage of cytokinesis, implicating RalA as a critical regulator of cell cycle progression. Cytokinesis is a crucial process in which the cytoplasmic constituents of the mother cell are divided into two identical daughter cells, ensuring the fidelity of cell division. Cytokinesis proceeds via distinct steps, including assembly of the actomyosin contractile ring, formation of the ingressing cleavage furrow, and cell cleavage or abscission (1Glotzer M. Science. 2005; 307: 1735-1739Crossref PubMed Scopus (563) Google Scholar). Membrane trafficking is important for all steps of cytokinesis and is directly required for sealing off the abscission site where cells undergo the final separation (2Strickland L.I. Burgess D.R. Trends Cell Biol. 2004; 14: 115-118Abstract Full Text Full Text PDF PubMed Scopus (61) Google Scholar). Recycling endosome-derived vesicle trafficking plays an essential role in the terminal stages of cytokinesis, possibly under the control of the centrosome (3Albertson R. Riggs B. Sullivan W. Trends Cell Biol. 2005; 15: 92-101Abstract Full Text Full Text PDF PubMed Scopus (168) Google Scholar). However, the mechanisms underlying this polarized delivery of vesicles from the recycling endosomes during abscission remain poorly understood.The exocyst is an evolutionarily conserved vesicle tethering complex, comprised by eight subunits including Sec3, Sec5, Sec6, Sec8, Sec10, Sec15, Exo70, and Exo84 (4Lipschutz J.H. Mostov K.E. Curr. Biol. 2002; 12: R212-R214Abstract Full Text Full Text PDF PubMed Google Scholar). This complex has been proposed to mediate the initial recognition between the exocytic vesicles and the target membrane, thereby contributing to the specificity and efficiency of certain vesicular transport processes (5Dong G. Hutagalung A.H. Fu C. Novick P. Reinisch K.M. Nat. Struct. Mol. Biol. 2005; 12: 1094-1100Crossref PubMed Scopus (109) Google Scholar). Recent insights into structure of the exocyst have shed light on the architecture and function of this complex, suggesting that the exocyst assembles into an overall rod-like structure, in the process bridging the vesicles to their target membrane (5Dong G. Hutagalung A.H. Fu C. Novick P. Reinisch K.M. Nat. Struct. Mol. Biol. 2005; 12: 1094-1100Crossref PubMed Scopus (109) Google Scholar, 6Sivaram M.V. Saporita J.A. Furgason M.L. Boettcher A.J. Munson M. Biochemistry. 2005; 44: 6302-6311Crossref PubMed Scopus (80) Google Scholar). Consistent with this notion, the exocyst has been found to concentrate on "hotspots" on the plasma membrane where exocytosis actively takes place and has been implicated in different types of membrane trafficking including polarized growth in yeast, neurite growth in the nervous system, glucose transport in fat cells, and basal-lateral trafficking in epithelial cells (4Lipschutz J.H. Mostov K.E. Curr. Biol. 2002; 12: R212-R214Abstract Full Text Full Text PDF PubMed Google Scholar). Interestingly, in Saccharomyces cerevisiae and Schizosaccharomyces pombe, the exocyst complex localizes to the cleavage furrow and is essential for membrane delivery during cytokinesis (7Dobbelaere J. Barral Y. Science. 2004; 305: 393-396Crossref PubMed Scopus (221) Google Scholar, 9Wang H. Tang X. Liu J. Trautmann S. Balasundaram D. McCollum D. Balasubramanian M.K. Mol. Biol. Cell. 2002; 13: 515-529Crossref PubMed Scopus (143) Google Scholar). However, the role of the exocyst in cytokinesis is poorly understood in mammalian cells, in which the exocyst has a more specialized yet complex function.Ral GTPases (RalA and RalB) have been the focus of special attention for their roles in regulating exocyst function in eukaryotic cells. Upon activation, Ral can bind two exocyst subunits, Sec5 and Exo84. RalA has higher affinity for these proteins than does RalB (10Shipitsin M. Feig L.A. Mol. Cell Biol. 2004; 24: 5746-5756Crossref PubMed Scopus (110) Google Scholar). Although the molecular mechanisms remain elusive, this unique interaction pattern may enable RalA to regulate the assembly of the exocyst during vesicle targeting as Sec5 and Exo84 seem to have different cellular localizations (11Jin R. Junutula J.R. Matern H.T. Ervin K.E. Scheller R.H. Brunger A.T. EMBO J. 2005; 24: 2064-2074Crossref PubMed Scopus (113) Google Scholar). Nevertheless, although RalA has been reported to regulate exocytosis in several scenarios, the generalized function of this ubiquitously expressed small GTPase in vesicle trafficking remains largely unknown. Importantly, RalA has also been implicated in signaling pathways controlling cell cycle progress, cell morphology, and oncogenic transformation (12Feig L.A. Trends Cell Biol. 2003; 13: 419-425Abstract Full Text Full Text PDF PubMed Scopus (200) Google Scholar). A recent report highlights the oncogenic function of RalA, but not RalB, and the involvement of the exocyst in RalA-induced cellular transformation (13Lim K.H. Baines A.T. Fiordalisi J.J. Shipitsin M. Feig L.A. Cox A.D. Der C.J. Counter C.M. Cancer Cell. 2005; 7: 533-545Abstract Full Text Full Text PDF PubMed Scopus (289) Google Scholar). However, it is not clear whether RalA-mediated vesicular trafficking is directly involved in cell cycle progression.Here we present data suggesting a critical role for RalA and the exocyst in targeting recycling endosome (RE) 2The abbreviations used are: RE, recycling endosome; RBD, Ral binding domain; TfR, transferrin receptor; MTOC, microtubule organization center; CHO, Chinese hamster ovary; PBS, phosphate-buffered saline; mAb, monoclonal antibody; siRNA, small interfering RNA. 2The abbreviations used are: RE, recycling endosome; RBD, Ral binding domain; TfR, transferrin receptor; MTOC, microtubule organization center; CHO, Chinese hamster ovary; PBS, phosphate-buffered saline; mAb, monoclonal antibody; siRNA, small interfering RNA.-derived trafficking during the completion of cytokinesis in mammalian cells. RalA is RE-associated and relocalizes to the cleavage furrow, and later, to the abscission site. The exocyst, through a spatially and temporally regulated association with key cytokinetic structures, regulates the targeting of RalA-containing vesicles from RE. Disruption of this process leads to late stage cytokinesis failure.EXPERIMENTAL PROCEDURESConstructs—Full-length Sec5 was obtained from a 3T3-L1 cDNA library by PCR and completely sequenced and then cloned into the pKH3 vector (14Inoue M. Chang L. Hwang J. Chiang S.H. Saltiel A.R. Nature. 2003; 422: 629-633Crossref PubMed Scopus (281) Google Scholar). Sec5 RBD-(1-120) and RalBP1 RBD-(397-519) were cloned into peYFP-C1 vector (BD Biosciences). Sec5 Ral-binding domain (RBD) T11A was generated using site-directed mutagenesis (Stratagene). RalA variants were cloned into pK-FLAG vector or peGFP-C3 vector (BD Biosciences).Cell Culture, Transfection, and Inhibitors—Cos-1 and HeLa cells were grown in Dulbecco's modified Eagle's medium supplemented with 10% fetal bovine serum and 100 units ml-1 streptomycin (Invitrogen). CHO cells were grown in Dulbecco's modified Eagle's medium/F-12 medium supplemented with the 10% fetal bovine serum and 100 units ml-1 streptomycin. Cos-1 cells were transfected using FuGENE 6 (Roche Applied Science) according to the manufacturer's directions. All chemicals and inhibitors were from Sigma. Cells were treated at 37 °C with 33 μm nocodazole for 2 h, 2 μm cytochalasin D for 1 h, 2 μm brefeldin A for 2 h, or 0.5% tannic acids for 10 min.Immuno-fluorescence and Antibodies—Cells were grown on glass coverslips and washed with PBS before fixation. After fixation with methanol at -20 °C for 3 min, cells were rehydrated in PBS and then blocked with 1% bovine serum albumin and 1% chicken albumin. For RBD experiments, cells were fixed with 10% formalin at room temperature for 10 min, neutralized with 100 mm glycine/PBS, and then permeabilized with 0.5% Triton X-100 before blocking. RalA localization remains the same in different fixation conditions. Primary antibodies used were α-tubulin (1:500, mAb), FLAG (1:500, rabbit IgG), and γ-adaptin(1:200, mAb) from Sigma; pericentrin (1:100, rabbit IgG) from Abcam; transferrin receptor (1:500, mAb), Rab11 (1:50, rabbit IgG) from Alpha Diagnostic; GM130 (1:100, mAb) from BD Biosciences; Sec8 (1:100, mAb) from Stressgen; hemagglutinin (1:500, mAb or rabbit IgG) from Santa Cruz Biotechnology. Monoclonal anti-Exo70 was described previously (18Polishchuk R. Di Pentima A. Lippincott-Schwartz J. Nat. Cell Biol. 2004; 6: 297-307Crossref PubMed Scopus (182) Google Scholar). Alexa Fluor-conjugated goat anti-mouse/rabbit secondary antibodies, Alexa Fluor-conjugated phalloidin, and Vector Shield mounting medium were from Molecular Probe. The following antibodies were used in biochemical assays: RalA, Rab4, Nek2, EEA1 mAbs were from BD Biosciences; rabbit anti-Exo84 was from Orbigen; rabbit anti-Sec10 was kindly provided by Dr.Wei Guo (University of Pennsylvania).Western Blots—Cells were washed with PBS and lysed for 30 min at 4 °C in buffer (buffer A) containing 100 mm Tris (pH 7.5), 1% Nonidet P-40, 135 mm NaCl, 1 mm EDTA, 1.0 mm sodium orthovanadate, 10 mm NaF, and protease inhibitor tablets (Roche Applied Science). The lysates were subjected to SDS-PAGE and transferred to nitrocellulose. Individual proteins were detected with specific antibodies and visualized by blotting with horseradish peroxidase-conjugated secondary antibodies.Midbody Prep—CHO cell midbody prep was performed according to a previous study (15Skop A.R. Liu H. Yates J. II I Meyer B.J. Heald R. Science. 2004; 305: 61-66Crossref PubMed Scopus (385) Google Scholar). The pellet fraction of interphase cells and cytokinetic cells treated with taxol and jas-plakinolide were subjected to SDS-PAGE and blotted with specific antibodies.Opti-Prep Gradient—Cos cells were washed with PBS, homogenized in HES buffer (20 mm Hepes, pH 7.4, 1 mm EDTA, 250 mm sucrose) 10 times with a ball-bearing homogenizer (Wheaton), and spun at 3,000 × g for 3 min to generate postnuclear supernatant. To generate a 10-20-30% continuous gradient, 1.2 ml of postnuclear supernatant was mixed 1:1 with 60% iodixanol (Opti-Prep) and layered under 1.3 ml of 20% iodixanol and 1.2 ml of 10% iodixanol, respectively. The gradient was spun at 72,000 rpm in a fixed angle NVT90 rotor for 3 h at 4 °C and fractionated into 25 fractions. An equal volume of each fraction was loaded in SDS-PAGE.siRNA Knockdown—The following siRNA oligonucleotides (Invitrogen) were used: RalA, 5′-CCAAGGGUCAGAAUUCUUU-3′ (oligonucleotide-1 sense), 5′-GCUAAUGUUGACAAGGUAU-3′ (oligonucleotide-2 sense); Sec8, 5′-CCUUGAUACCUCUCACUAU-3′ (oligonucleotide-1 sense), 5′-GCUUUCUCCAAUCUUUCUA-3′ (oligonucleotide-2 sense). Control oligonucleotides with medium GC content or fluorescent labeling were also from Invitrogen. 100 nm oligonucleotides were transfected into HeLa cells using Oligofectamine according to the manufacturer's instructions. After 3 days, cells were trypsinized and replated at low density, and a second round of knockdown was performed. Cells were either harvested in SDS-PAGE sample buffer for Western blot or fixed for immunofluorescent microscopy.Time-lapse Microscopy—Cos cells expressing eGFP-RalA were treated with 100 nm nocodazole for 16 h. The mitotic cells were harvested by centrifuge and released into the cell cycle for 30-40 min before being imaged at 37 °C using an upright fluorescent spinning disk microscope (Leica). Images were taken under a ×63 oil lens at 30-s intervals.RESULTSActive Ral GTPase Is Localized on the Pericentrosomal Membrane and at the Centrosome—To explore the function of the Ral GTPase, we generated an eYFP-tagged RBD of Sec5 to probe the localization of active Ral in vivo. In contrast to previous studies in polarized Madin-Darby canine kidney cells (16Moskalenko S. Henry D.O. Rosse C. Mirey G. Camonis J.H. White M.A. Nat. Cell Biol. 2002; 4: 66-72Crossref PubMed Scopus (349) Google Scholar, 17Moskalenko S. Tong C. Rosse C. Mirey G. Formstecher E. Daviet L. Camonis J. White M.A. J. Biol. Chem. 2003; 278: 51743-51748Abstract Full Text Full Text PDF PubMed Scopus (179) Google Scholar), the fluorescent fusion protein mainly decorated the perinuclear region in the cytoplasm of quiescent Cos-1 cells rather than the plasma membrane (Fig. 1a, upper panel). We noticed that this fluorescent protein also localized to the nucleus as green fluorescent protein is known to non-specifically diffuse throughout the cytoplasm and nucleus. The nuclear-localized fluorescent RBDs, however, may be isolated from Ral in the cytoplasm due to the presence of the nuclear envelope and thus cannot function as probes for activated Ral. Interestingly, in ∼20% of the transfected cells, Sec5 RBD decorated one or two bright dots near the nucleus. Co-staining with α-tubulin reveals that Sec5 RBD localized to the centrosome in interphase cells, as well as the centrosome-related abscission site in cells undergoing cytokinesis (Fig. 1a, lower panel). The same results were obtained with the RBD from RalBP1, another Ral-interacting protein (Fig. 1b). Nevertheless, Sec5 RBD T11A showed a distinct localization and did not concentrate at the pericentrosomal region (Fig. 1c and supplemental Fig. S1b) due to its substantially lower affinity for active Ral (supplemental Fig. S1a). Taken together, the data indicate that endogenous Ral can be activated at the centrosomal and pericentrosomal membranes.Several recent studies have implicated Ral GTPase in vesicle trafficking (12Feig L.A. Trends Cell Biol. 2003; 13: 419-425Abstract Full Text Full Text PDF PubMed Scopus (200) Google Scholar), although the exact mechanism remains to be elucidated. We found that ectopically expressed RalA also co-localized with eYFP-RBDs in the same pericentrosomal tubule-vesicular structures, suggesting that a large fraction of active RalA associates with intracellular membranes in addition to the plasma membrane (supplemental Fig. S1c). Indeed, we observed that wild type RalA localized to the vesicular structures surrounding the centrosome/microtubule organization center and associated with the microtubule filament (Fig. 1d).RalA Is an RE-localized GTPase That Relocalizes during Cell Division—Despite the general notion that RalA can localize to the exocytotic vesicles in some specialized cells such as neurons and platelets (12Feig L.A. Trends Cell Biol. 2003; 13: 419-425Abstract Full Text Full Text PDF PubMed Scopus (200) Google Scholar), the exact subcellular localization of this widely expressed GTPase is unclear. The pericentrosomal localization of RalA closely resembles the Golgi apparatus or the recycling endosome, two organelles often organized around the microtubule organization center. Consistent with a study in polarized Madin-Darby canine kidney cells by Shipitsin and Feig (10Shipitsin M. Feig L.A. Mol. Cell Biol. 2004; 24: 5746-5756Crossref PubMed Scopus (110) Google Scholar), we observed that RalA co-localized with the recycling endosome markers TfR and partially with Rab11 in non-polarized Cos-1 cells but poorly with GM130 or γ-adaptin, which decorate the cis and trans Golgi membrane, respectively (Fig. 2a). In addition, disruption of the microtubule network by nocodazole or inhibition of vesicle flow by tannic acid (18Polishchuk R. Di Pentima A. Lippincott-Schwartz J. Nat. Cell Biol. 2004; 6: 297-307Crossref PubMed Scopus (182) Google Scholar) abolished the pericentrosomal localization of RalA, whereas disassembly of Golgi by brefeldin A had little effect (supplemental Fig. S2).FIGURE 2RalA is an RE-localized GTPase that relocalizes during cell division. a, RalA co-localizes with TfR and Rab11 but not with γ-adaptin or GM130. Cos-1 cells transfected with eGFP-RalA wild-type cells were stained with antibodies against the indicated proteins (red). b, nocodazole treatment causes RalA to localize to punctuate structures that co-localize with TfR but not with GM130. c, cellular fractionation profile of RalA. Cos-1 cells were homogenized, and the postnuclear supernatant was separated using a linear 10-20-30% Opti-Prep gradient. An equal volume of each fraction was loaded on a 4-20% SDS-PAGE gel. Distribution of different proteins was determined by Western blot. d, cell cycle-dependent relocalization of RalA. Cos-1 cells expressing eGFP-RalA wild-type cells were stained with α-tubulin (red) antibody to determine the stages in cell cycle.View Large Image Figure ViewerDownload Hi-res image Download (PPT)Nocodazole is able to disrupt the pericentrosomal localization of both recycling endosomes and the Golgi apparatus, separating these organelles into geographically distinct structures. We used this approach to further define the localization of RalA. As expected, RalA precisely co-localized with TfR in peripheral vesicular structures but not with GM130 (Fig. 2b), suggesting a preferred localization of RalA to the recycling endosome but not to Golgi. Furthermore, endogenous RalA partially overlapped with the TfR and Rab11 but not with the early endosome marker EEA1, the Golgi protein Syntaxin-6, or the cytosolic protein Akt in a linear Opti-Prep gradient (Fig. 2c). Notably, RalA also co-fractionated with Rab4, another GTPase known to regulate endosome recycling, suggesting the similar properties of the vesicular membranes marked by these GTPases. Taken together, we conclude that RalA localizes to a subset of recycling endosomes in both polarized and non-polarized cells, suggesting an important role of RalA in regulating vesicle trafficking via the endocytotic recycling route.Interestingly, we observed that RalA underwent cell cycle-dependent relocalization (Fig. 2d) similar to certain RE proteins involved in vesicle trafficking during cytokinesis (19Hickson G.R. Matheson J. Riggs B. Maier V.H. Fielding A.B. Prekeris R. Sullivan W. Barr F.A. Gould G.W. Mol. Biol. Cell. 2003; 14: 2908-2920Crossref PubMed Scopus (113) Google Scholar, 20Wilson G.M. Fielding A.B. Simon G.C. Yu X. Andrews P.D. Hames R.S. Frey A.M. Peden A.A. Gould G.W. Prekeris R. Mol. Biol. Cell. 2005; 16: 849-860Crossref PubMed Scopus (234) Google Scholar). Co-staining of cells with α-tubulin revealed that RalA localized predominantly to the plasma membrane in mitosis, during which endosome recycling stops. However, upon the initiation of anaphase, RalA was targeted to the ingestion furrow, and later, to the intracellular bridge. Moreover, during the final step of cytokinesis, RalA localized to the abscission site, indicating a role for RalA in vesicle trafficking during the completion of cytokinesis.The Exocyst Is Spatially and Temporally Localized during the Cell Cycle—RalA has been implicated in polarized trafficking through its interaction with the exocyst complex, which plays an essential role in vesicle targeting during cytokinesis in lower organisms (7Dobbelaere J. Barral Y. Science. 2004; 305: 393-396Crossref PubMed Scopus (221) Google Scholar, 9Wang H. Tang X. Liu J. Trautmann S. Balasundaram D. McCollum D. Balasubramanian M.K. Mol. Biol. Cell. 2002; 13: 515-529Crossref PubMed Scopus (143) Google Scholar). We thus postulated that the exocyst complex may also facilitate polarized vesicle trafficking during mammalian cytokinesis. Immuno-fluorescence microscopy showed a punctate localization throughout the cell for the exocyst subunit Sec8, which accumulated in the juxtanuclear region where it co-localized with the centrosome marker pericentrin. During mitosis and cytokinesis, however, Sec8 associated with the mitotic apparatus, including the spindle poles, and with cytokinetic structures, including the central spindles and the midbody (Fig. 3a). The same results were obtained using a different Sec8 antibody (data not shown). Another exocyst protein, Exo70, is also localized around and at the centrosome, and later, the midbody (supplemental Fig. S3), as is the overexpressed exocyst protein Sec5 (Fig. 3b) and Sec8 (data not shown). Notably, ectopic expression revealed that the exocyst proteins are enriched in the abscission site, indicating that the exocyst may also regulate vesicular trafficking to the abscission site of the dividing cells. This enrichment was not visualized by endogenous protein staining, possibly due to epitope masking, a common technical difficulty in midbody staining. A recent proteomics study profiling midbody-associated proteins revealed that the exocyst subunit Sec3 is associated with the midbody (15Skop A.R. Liu H. Yates J. II I Meyer B.J. Heald R. Science. 2004; 305: 61-66Crossref PubMed Scopus (385) Google Scholar). Indeed, we found that the exocyst proteins and RalA are present in biochemically isolated midbody from synchronized CHO cells (Fig. 3c), further suggesting that these proteins may participate in membrane trafficking during cytokinesis.FIGURE 3The exocyst is spatially and temporally regulated during the cell cycle. a, cell cycle-dependent relocalization of Sec8. Cos-1 cells were stained using antibodies against pericentrin (green) and Sec8 (red). Sec8 localizes to the centrosome during interphase and then concentrates on mitotic spindles (mitosis), central spindles (anaphase), and the midbody (cytokinesis). b, Cos-1 cells were transfected with hemagglutinin-Sec5 full-length and stained with antibody against pericentrin (green) and hemagglutinin (HA) (red). Cytokinetic cells with different expression levels of Sec5 were shown. c, biochemical evidence that the exocyst associates with the midbody. Midbody isolation was performed according to standard methods (15Skop A.R. Liu H. Yates J. II I Meyer B.J. Heald R. Science. 2004; 305: 61-66Crossref PubMed Scopus (385) Google Scholar) with cytokinetic CHO cells or unsynchronized cell as control. Total cell lysate and pellets of the above experiment were subjected to SDS-PAGE followed by Western blot for the indicated proteins. DIC, differential interference contrast.View Large Image Figure ViewerDownload Hi-res image Download (PPT)Disruption of RalA-Exocyst Function Causes Late Stage Cytokinesis Failure—The dynamic relocalization of RalA and the exocyst to cytokinetic structures led us to investigate their potential roles in cell cycle progress. We observed that overexpression of RalA in Cos-1 cells leads to a moderate increase of binucleated cells (Fig. 4a, upper panel), a phenotype commonly resulting from cytokinesis failure. However, we also observed that a significant fraction of the cells form two-cell syncytia connected by microtubule bundles, and one cell body shrinks and often detaches from the culture substrate (Fig. 4a, lower panel, and Fig. 4c). To investigate this phenomenon in detail, we performed live cell imaging on Cos-1 cells overexpressing eGFP-RalA (Fig. 4b). We found that upon the initiation of cytokinesis, RalA was transported to the intracellular bridge in vesicular bodies and also localized to the plasma membrane of the cleavage furrow, similar to what was visualized in fixed cells. As cytokinesis proceeds, RalA associates with the abscission sites localized at the center of the intracellular bridge. However, the cells remain interconnected for a long period of time (≥6 h after the initiation of cytokinesis), as determined by the persistent abscission site marked by eGFP-RalA, and finally, one cell collapses, possibly due to the increased cellular tension or triggering of apoptosis after failed cytokinesis (21Reichl E.M. Effler J.C. Robinson D.N. Trends Cell Biol. 2005; 15: 200-206Abstract Full Text Full Text PDF PubMed Scopus (49) Google Scholar).FIGURE 4Disruption of RalA-exocyst function results in late stage cytokinesis failure. a, overexpression of RalA leads to formation of binucleated cells (upper panel) and cell syncytia with persistent intracellular bridge (lower panel). Cos-1 cells were transfected with eGFP-RalA for 36 h and stained with α-tubulin (red) antibody. b, live cell images were taken on Cos-1 cells expressing eGFP-RalA at 30-s intervals. The arrows indicate the abscission site at the middle of the intracellular bridge. c, the percentage of cells that form syncytia when RalA was overexpressed. d, HeLa cells transfected with indicated siRNA oligonucleotides were stained with antibodies against pericentrin (green) and α-tubulin (red). The nucleus was visualized by 4′,6-diamidino-2-phenylindole (blue); images were taken on an epi-fluorescence microscope. The arrows indicate the persistent intracellular bridges connecting daughter cells together. Mock, mock-transfected. e, HeLa cells were transfected with 100 nm indicated siRNA oligonucleotides and lysed in SDS-containing buffer. Cellular protein levels were determined by Western blot following SDS-PAGE. Control oligo, control oligonucleotide; oligo1, oligonucleotide-1; oligo2, oligonucleotide-2. f, the percentage of the cells after siRNA transfection showing cell cycle defects. Cells were categorized into binucleated, cytokinetic or syncytia, or undetermined if the cells were too close to be determined. KD, kinase-deficient.View Large Image Figure ViewerDownload Hi-res image Download (PPT)To further address the function of RalA and the exocyst in cytokinesis, we used siRNA-mediated knockdown to deplete cellular expression of RalA and Sec8 in HeLa cells. The efficiency of the knockdown was verified by fluorescent oligonucleotides (data not shown) and Western blot (Fig. 4e). When examined by immunofluorescence microscopy, both Sec8 and RalA knockdown in HeLa cells led to an increased number of binucleated cells. However, a significant percentage of cells formed syncytia with two, three, or four cells that are connected with prolonged yet stretched intracellular bridges (Fig. 4, d and f). These multicell syncytia may arise from failed cytokinesis following a second round of mitosis of the individual cells since one of the connected cells can re-enter mitosis. Taken together, the data indicate that disruption of the RalA-exocyst function leads to a late stage cytokinesis failure, likely resulting from incomplete abscission.DISCUSSIONMembrane trafficking is an essential but poorly understood step in cytokinesis (3Albertson R. Riggs B. Sullivan W. Trends Cell Biol. 2005; 15: 92-101Abstract Full Text Full Text PDF PubMed Scopus (168) Google Scholar). We report here a critical role of the exocyst, as well as its interacting GTPase RalA, in directing membrane trafficking to the key cytokinetic structures in mammalian systems. Our data suggest that besides fulfilling a general need for membrane addition, the exocyst may mediate the delivery of a specific set of vesicles to the abscission site.The data described here support the idea that RE-derived membrane trafficking is crucial for the completion of cytokinesis (3Albertson R. Riggs B. Sullivan W. Trends Cell Biol. 2005; 15: 92-101Abstract Full Text Full Text PDF PubMed Scopus (168) Google Scholar, 20Wilson G.M. Fielding A.B. Simon G.C. Yu X. Andrews P.D. Hames R.S. Frey A.M. Peden A.A. Gould G.W. Prekeris R. Mol. Biol. Cell. 2005; 16: 849-860Crossref PubMed Scopus (234) Google Scholar) and point to a novel mechanism underlying this polarized vesicle delivery event. We found that RalA is localized and activated on RE and RE-derived vesicles. Moreover, RalA is spatially and temporally regulated during cell division, coupled with the relocalization of exocyst proteins to cytokinetic structures. Disruptions of RalA or exocyst function lead to similar cell cycle defects. Taken together, these